2008
DOI: 10.1161/atvbaha.107.159772
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Lipid Raft Redox Signaling Platforms in Endostatin-Induced Coronary Endothelial Dysfunction

Abstract: Objective-Endostatin (EST) was found to initiate a redox signaling cascade associated with activation of NADPH oxidase in endothelial cells (ECs). The present study tested whether EST stimulates clustering of ceramide-enriched lipid rafts (LRs), which assembles and activates NADPH oxidase to form redox signaling platforms. Methods and Results-Using confocal microscopy, we first demonstrated a colocalization of LR clusters with NADPH oxidase subunits, gp91 phox and p47 phox in the ECs membrane on EST stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 44 publications
7
94
0
Order By: Relevance
“…The siRNA of ASM gene was purchased from QIAGEN, which has been proven to be efficient to knock down the ASM gene in CAECs by our laboratory's previous studies (20,40) and was further confirmed in the present study (Supplemental Fig. 1).…”
Section: Immunofluorescent Microscopic Analysis Of Lr Clusterssupporting
confidence: 76%
“…The siRNA of ASM gene was purchased from QIAGEN, which has been proven to be efficient to knock down the ASM gene in CAECs by our laboratory's previous studies (20,40) and was further confirmed in the present study (Supplemental Fig. 1).…”
Section: Immunofluorescent Microscopic Analysis Of Lr Clusterssupporting
confidence: 76%
“…Previous studies have demonstrated that the formation of MR-redox signaling platforms in the EC membrane is associated with ceramide production via lysosomal ASM, which is translocated to the plasma membrane via membrane proximal lysosome trafficking and fusion after stimulation (Jin et al, 2008b;Bao et al, 2010a,b). Ceramides spontaneously fuse MRs into large ceramide-enriched membrane domains, which can serve as MR-redox signaling platforms (Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…When cells were grown to ϳ70 -80% confluence, human recombinant TNF-␣ (PeproTech, Rocky Hill, NJ) was added to the medium in a final concentration of 20 ng/ml for 15 min in the presence or absence of MCD (10 mmol/l; Sigma, St. Louis, MO), desipramine (DES, 10 M, Sigma), apocynin (Apo, 3 M, Sigma), or diphenyleneiodonium (DPI, 1 M, Sigma). Doses of compounds used in these experiments were based on our previous studies and some preliminary data showing that they could effectively inhibit corresponding cell responses (13,22,38,50).…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for Western blot analysis were described in detail in our previous publications (22,49). For immunodetection of LR-associated proteins, 50 l of resuspended proteins were subjected to SDS-PAGE, transferred onto a nitrocellulose membrane, and blocked as described previously (50).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation